The perceptions of educators towards inclusive education in a sample of government primary schools. - Blackie, Cara (My University, 2012)
This study examined the perceptions of educators towards inclusive education. The educators’ perceptions of the barriers to learning, the skills required in an inclusive environment, the involvement of support in inclusive education and the training programmes required were all examined. Education White Paper 6 was introduced in 2001 by the South African Department of Education stipulating inclusive education policies and a long term goal of successful implementation of inclusive education country wide. The sample of this study consisted of forty educators from six government primary schools in the Johannesburg region. The questionnaire was created to look at educators perceptions of all aspects of inclusive education within their school. The results demonstrated an equal amount of positive and negative perceptions towards the implementation of inclusive education. The educators of this study reported perceiving themselves to be inadequately trained to assume the responsibilities of inclusive education. The perceived prevalent barriers to learning in the classroom were emotional and cognitive barriers to learning. Due to South Africa’s diverse population language was also seen to be a prominent barrier to learning within these schools. Educators reported the need for parental support for the successful implementation of inclusive education; however, the reality of these educators is that parental support is minimal and often nonexistent. Finally the limitations of the study are discussed and suggestions for further research made.